(untitled) (Journal of Dhaka Medical College, 2018)
Background: Abnormal glucose metabolism is an independent risk factor for poor outcome following acute ischemic stroke. Objective: To evaluate the association between high HbA1c level and poor functional outcome in new onset ischemic stroke patient with diabetes mellitus. Method: This Cross sectional study was carried out in the Department of Neurology, BSMMU, Dhaka, from February 2013 to September 2014 on 50 patients with first attack of ischemic stroke with DM. modified Rankin Scale (mRS) and HbA1c were measured on 14th day of the stroke. During this period other important relevant investigations were also recorded. Result: Majority of the patients (40.0%) were in age group 51-60 years. The mean age was 58.9 ± 9.6 years with a range from 30 to 75 years. Males were 52.0% and females were 48.0%. Male to female ratio was 1.08:1. It was observed that more than one third (36.0%) patients were current smoker, 9(18.0%) were former smoker and 23(46.0%) were non smoker. Majority of the 29(58.0%) patients had hypertension. Mean systolic BP was found 129 ±16 mmHg with a range from 90 to 160 mmHg. The mean diastolic BP was found 81±11 mmHg with a range from 60 to 100 mmHg. HbA1c has significant positive correlation with modified ranking scale on 14th day of stroke [r= 0.504 (p<0.001)]. Conclusion: As per study result it can be concluded that increase level of HbA1c is associated with higher level of mRS. J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 5-8